DETERMINASI TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Dinda Oktaviyanti (2021)
This study aims to determine the effect of Income Tax, Tunneling Incentive, and Debt Covenant on Transfer Pricing indications. This study uses all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2015-2019. The sampling technique used was purposive sampling method. Selection of a sample of 105 manufacturing companies. Hypothesis testing used is Logistic Regression Analysis with SPSS 25 program and a significant level of is 5% (0.05). The results of this testing showed that (1) there is no influence of income tax, as measured by Book Tax Different (BTD) on transfer pricing with a significant level of 0.822 is greater than the determined level α = 0.05, (2) there is an effect of tunneling. Incentive, which is measured based on the amount of foreign share ownership that exceeds 20% on Transfer Pricing with a significant level of 0.011, smaller than the specified level α = 0.05, and (3) there is no effect of Debt Covenant, as measured by the Debt to Equity Ratio (DER) on transfer pricing with a significant level of 0.340 which is greater than the specified level α = 0.05.